2007
DOI: 10.1016/j.npep.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin selectively increases ERα mRNA in the neonatal hypothalamus and hippocampus of female prairie voles

Abstract: During neonatal development exogenous oxytocin increases ERα immunoreactivity in the hypothalamus of female prairie voles. The purpose of this study was to determine if the increase in ERα is associated with an increase in ERα mRNA expression and to determine if the effect is specific to ER subtype or if oxytocin also influences ERβ mRNA expression. On the day of birth female prairie vole pups were treated with oxytocin, an oxytocin antagonist, or saline. Brains were collected and RT-PCR was used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…This programming phenomenon was first described in rats (Swaab and Boer, 1983;Boer, 1993;Boer et al, 1994) and named 'hormonal imprinting' by Csaba (1986). Reviewed in Bales and Perkeybile (2012), single doses of oxytocin given to newborn prairie vole pups have long-term sex-specific consequences on PVN oxytocin and on other systems such as V1aR and estrogen receptor alpha (Yamamoto et al, 2004(Yamamoto et al, , 2006Kramer et al, 2006;Bales et al, 2007a;Pournajafi-Nazarloo et al, 2007). For example, as adults, prairie voles treated with a single dose of oxytocin or an OXTR antagonist given intraperitoneally on postnatal day 1 had altered levels of V1aR in various brain regions in a sex-dependent manner (Bales et al, 2007a), although surprisingly, no treatment effects on OXTR or the dopamine D2 receptor were observed.…”
Section: Oxytocin and Vasopressin Impact Brain Developmentmentioning
confidence: 99%
“…This programming phenomenon was first described in rats (Swaab and Boer, 1983;Boer, 1993;Boer et al, 1994) and named 'hormonal imprinting' by Csaba (1986). Reviewed in Bales and Perkeybile (2012), single doses of oxytocin given to newborn prairie vole pups have long-term sex-specific consequences on PVN oxytocin and on other systems such as V1aR and estrogen receptor alpha (Yamamoto et al, 2004(Yamamoto et al, , 2006Kramer et al, 2006;Bales et al, 2007a;Pournajafi-Nazarloo et al, 2007). For example, as adults, prairie voles treated with a single dose of oxytocin or an OXTR antagonist given intraperitoneally on postnatal day 1 had altered levels of V1aR in various brain regions in a sex-dependent manner (Bales et al, 2007a), although surprisingly, no treatment effects on OXTR or the dopamine D2 receptor were observed.…”
Section: Oxytocin and Vasopressin Impact Brain Developmentmentioning
confidence: 99%
“…This is not obvious as in a previous murine model likening the human condition of obesity and leptin resistance, and displaying an high bone mass phenotype, as the ob / ob mice, a dramatic increase in food consumption was also reported, 3 whereas in another case of leptin resistance as the murine model of Oxt deficiency, an increased WAT and high bone mass in spite of no changes in food intake has been observed. 7,8 The expression of oxytocin and oxytocin receptor in central and peripheral tissues is ER-dependent 16 then it is plausible to speculate that the genetic manipulation of ER-signalling in neuronal cells could also lead to the failure of oxytocin signal in the brain. This could have contributed to the high bone mass reported in nestin-ER − / − mice.…”
Section: Commentarymentioning
confidence: 99%
“…A follow-up study indicated that during the neonatal period OT may affect the expression of ER ␣ by influencing the production of ER ␣ mRNA [Pournajafi-Nazarloo et al, 2007a]. On the day of birth female prairie vole pups were treated with OT, OTA or saline (as above).…”
Section: Estrogen Receptors Are Also Affected By Neonatal Manipulatiomentioning
confidence: 99%